How does poverty affect children's nutritional status in Nairobi slums? A qualitative study of the root causes of undernutrition. Issue 4 (20th September 2016) - Goudet, Sophie M; Kimani-Murage, Elizabeth W; Wekesah, Frederick; Wanjohi, Milka; Griffiths, Paula L; Bogin, Barry; Madise, Nyovani J
Abstract: Objective: Children in slums are at high risk of undernutrition, which has long-term negative consequences on their physical growth and cognitive development. Severe undernutrition can lead to the child's death. The present paper aimed to understand the causes of undernutrition in children as perceived by various groups of community members in Nairobi slums, Kenya. Design: Analysis of ten focus group discussions and ten individual interviews with key informants. The main topic discussed was the root causes of child undernutrition in the slums. The focus group discussions and key informant interviews were recorded and transcribed verbatim. The transcripts were coded in NVivo by extracting concepts and using a constant comparison of data across the different categories of respondents to draw out themes to enable a thematic analysis. Setting: Two slum communities in Nairobi, Kenya. Subjects: Women of childbearing age, community health workers, elders, leaders and other knowledgeable people in the two slum communities ( n 90). Results: Participants demonstrated an understanding of undernutrition in children. Conclusions: Findings inform target criteria at community and household level that can be used to identify children at risk of undernutrition. To tackle the immediate and underlying causes of undernutrition, interventions recommended should aim to: (i) improve maternal health and nutrition; (ii) promote optimal infant and young children feeding practices; (iii) support mothers in their working role; (iv) increase access to family planning; (v) improve water, sanitation and hygiene (WASH); (vi) address alcohol problems at all levels; and (vii) address street food issues with infant feeding counselling.